Improving Student Motivation and Reading Skill by Using Literature Circles - Haeroni Hani; Nurhaedah Gailea (Journal of English Language Teaching and Cultural Studies, 2018)
The objective of this research is to find out the improvement of motivation and reading skill by using literature circles in SMAN 1 Cinangka. The researcher used classroom action research. The sample of this research is students who sit in the eleventh grade of SMAN 1 Cinangka with 35 students. There are three cycles which was used by the researcher.  In order to improve the motivation and reading skill, literature circles was implemented in four weeks. In the last circle pre-cycle and post cycle were compared. The researcher found that there is significant improving of motivation and reading skill by using literature circles. The first cycle students reading skill improved 42,9%, and the students  motivation improved 41,%. The second cycle gradually students reading skill improved 68,6%, and the students motivation improved 80,%. The third cycle students reading skill improved 91,4%, and the students motivation improved 91,4,%. It means that there is significant improvement of motivation and skill which focused on discerning main idea, specific information, understanding the sequence, and inference, in SMAN 1 Cinangka by using literature circles. All these suggest that improving reading motivation and skill by using literature circles is highly encourage.